1997
DOI: 10.1128/mcb.17.6.3242
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Analysis of Rts1p, a B′ Regulatory Subunit of Saccharomyces cerevisiae Protein Phosphatase 2A

Abstract: The Saccharomyces cerevisiae gene RTS1 encodes a protein homologous to a variable B-type regulatory subunit of the mammalian heterotrimeric serine/threonine protein phosphatase 2A (PP2A). We present evidence showing that Rts1p assembles into similar heterotrimeric complexes in yeast. Strains in which RTS1 has been disrupted are temperature sensitive (ts) for growth, are hypersensitive to ethanol, are unable to grow with glycerol as their only carbon source, and accumulate at nonpermissive temperatures predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 49 publications
(71 reference statements)
5
112
1
Order By: Relevance
“…Deconvolution reveals that cln3⌬ cells show roughly equal proportions of G 1 and S phase cells, but no other phases. For each of the other strains, the observed deconvolution results match the defects observed by other techniques (17)(18)(19)(20)(21), such as the known post-S phase delay of cells overexpressing calmodulin [CMD1 (Tet)], which are defective in nuclear division (22), exhibiting a higher proportion of M and M͞G 1 cells in our analysis.…”
Section: Validation Of Expression Deconvolution Analysissupporting
confidence: 75%
“…Deconvolution reveals that cln3⌬ cells show roughly equal proportions of G 1 and S phase cells, but no other phases. For each of the other strains, the observed deconvolution results match the defects observed by other techniques (17)(18)(19)(20)(21), such as the known post-S phase delay of cells overexpressing calmodulin [CMD1 (Tet)], which are defective in nuclear division (22), exhibiting a higher proportion of M and M͞G 1 cells in our analysis.…”
Section: Validation Of Expression Deconvolution Analysissupporting
confidence: 75%
“…Previous studies suggested that Rts1 is a phospho-protein (Shu et al 1997), which suggested that feedback signals could be relayed via phosphorylation of Rts1. To investigate further, we raised an antibody that recognizes Rts1.…”
Section: Pp2a Rts1 Is Controlled By Ceramide-dependent Signalsmentioning
confidence: 99%
“…TPD3 encodes the only A subunit, and two distinct B subunits, encoded by CDC55 and RTS1, are highly homologous to mammalian B and BЈ, respectively (7)(8)(9). Mutations of CDC55 are viable, but yield defects in cytokinesis and in the spindle checkpoint and result in abnormal cell morphology.…”
mentioning
confidence: 99%